PENGARUH LAYANAN BIMBINGAN KARIR TERHADAP PERENCANAAN KARIR SISWA KELAS IX F SMP NEGERI 3 PONTIANAK - Nurhidayah; Asrori, Muhammad; Yanti, Elli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Career planning is an important aspect that students need to develop starting from junior high school, as at this stage students begin to face choices regarding further education and future career directions. However, there are still students who do not yet have mature career planning, such as a lack of understanding and information about education and the world of work. Therefore, career guidance services in schools play an important role in helping students prepare their career planning optimally. This study aimed to determine the effect of career guidance services on the career planning of class IX F students at SMP Negeri 3 Pontianak. This research was causal research using a descriptive method. The research subjects consisted of 29 students selected through purposive sampling technique. Data were collected using a validated questionnaire instrument with a Likert scale. Data analysis employed Product Moment Correlation and the Coefficient of Determination. The results showed that career guidance services and students’ career planning were in the moderate category, with percentage ranges from 43.97% to 58.62%. Statistical analysis indicated a strong and significant relationship between the two variables, with a correlation coefficient value of 0.734 and a significance value of 0.000 (<0.05). Career guidance services contributed 53.9% to students’ career planning. The conclusion of this study indicates that the more optimal the career guidance services provided, the better the students’ career planning will be.